THE IMAGES OF SUBSURFACE TERTIARY – QUARTENARY DEPOSITS BASED ON GROUND PENETRATING RADAR RECORDS OF SUBI KECIL ISLAND COAST, NATUNA DISTRICT, RIAU ARCHIPELAGO PROVINCE - Kris Budiono (BULLETIN OF THE MARINE GEOLOGY, 2013)
Subsurface Tertiary to Quaternary deposits from coast of Subi Kecil Island, Natuna Distric, Riau Archipelago Province, were imaged with Ground Penetrating Radar (GPR). The GPR survey was carried out by using GSSI Surveyor III/20 with 270 MHz and 40 MHz of 3200 MLF antennas. GPR data were processed using software GSSI’s RADAN for Windows NT™. The interpretation were done by using the radar facies as a groups of radar reflections. The GPR images of study area can be recoqnized in to several facies such as parallel, sub parallel, chaotic, oblique, mound and reflection-free. The calibration were done with geological data along the coast (cliff and outcrop). Unit A is the uppermost layer which is characterized by continous to non continous pararel reflection, srong reflector and high amplitude and is interpreted as alluvium deposits. Below the unit A is unit B which is characterized by non continous sub parallel, chaotic and mound reflector, strong reflector and high amplitude. Unit C and D (Mio-Oligocene) are overlain by unit A and B include chaotic, reflection-free and, locally, discontinuous parallel, oblique mound reflector radar facies, correlatable at the cliff face to massive sands, mostly representing near coastal deposits. These units are bounded by continuous, high amplitude reflections that can be easily correlatable throughout the GPR profiles, serving as important stratigraphic markers. The GPR survey may improve the reconstruction of the depositional environments through the recognition of massive and unconsolidated sand deposits within unit A and B (Holocene). The stratigraphic framework was also improved through the recognition of the discontinuity surface between Units C and D. Keywords: radar facies, stratigraphy, Tertiary to Quatenary, Subi Kecil Island Pencitraan endapan bawah permukaan Tersier sampai Kuarter di pantai Pulau Subi Kecil, Natuna, Propinsi Riau Kepulauan, telah dilakukan dengan “Ground Penetrating Radar (GPR). Survey GPR dilakukan menggunakan SIR 20 GSSI dengan antenna 200 MHz, 40 MHz da MLF 3200. Data GPR diproses mengunakan perangkat lunak Radan GSSI untuk Window NTTM. Citra Radar di daerah penelitian dapat dibagi menjadi reflektor paralel, sub paralel, chaotik, oblik, undulasi dan bebas refleksi. Kalibrasi telah dilakukan dengan kondisi geologi sepanjang pantai (tebing dan singkapan batuan). Unit A merupakan lapisan paling atas, dicirikan oleh reflektor parallel yang menerus dan tidak menerus, reflektor kuat, amplitudo tinggi dan ditafsirkan sebagai endapan alluvium. Di bawah unit A adalah unit B yang dicirikan oleh reflektor sub paralel yang menerus sampai tidak menerus, chaotic, hiperbolik, dengan reflektor kuat dan amplitudo tinggi. Unit C dan D (Mio-Oligosen) ditutupi oleh unit B yang dicirikan oleh fasies reflektor chaotic, bebas reflektor, dan secara lokal pararel tidak menerus, miring dan hiperbolik, dapat dikorelasikan dengan pasir padat pada tebing sebagai endapan dekat pantai. Citra GPR memperlihatkan rekonstruksi lingkungan pengendapan melalui pengenalan pasir padat dan pasir lepas pada unit A dan B (Holosen). Kerangka stratigrafi akan lebih baik melalui pengenalan ketidak menerusan lapisan antara unit C dan D. Kata kunci: fasies radar, stratigrafi, Tersier sampai Kuarter, Pulau Subi Kecil